Analysis Customer Relationship Management (CRM) for increase Competitive Advantage in Water Tourism “ Jiput ” Kediri City - Rahmadi, Afif Nur; Sandi Eka Suprajang; Alma Hariyati; Yulia Kristina (Universitas Kadiri, 2024)
T he purpose of this study is to evaluate the implementation of a CRM system can improve the visitor experience through personalization of service, rapid response to feedback, and better relationship management . Analyzing and describing Customer Relationship Management ( CRM ) can help in increasing Competitive Advantage in Water Tourism